Tinjauan Hukum Islam dan Undang-Undang Nomor 41 Tahun 2004 tentang Wakaf terhadap Status Iuran Wakaf Tanah Kuburan - Siti Aulia Nur Hamidah; Iwan Permana; Liza Dzulhijjah (Bandung Conference Series: Sharia Economic Law, 2024)
Abstract. The issue of waqf has been regulated in the Waqf Law. However, the regulation of this problem does not necessarily eliminate all waqf problems, such as the issue of cemetery land waqf contributions. This study aims to find out the practice of waqf contributions and to find out the ownership status of the contributions purchased from land in the RW 001 area, Cigondewah Kaler Village based on a review of Islamic law and Law Number 41 of 2004 concerning Waqf. This type of research is qualitative research using an empirical normative approach. The data sources used are primary data and secondary data. Data collection in the study uses interviews, observations and literature studies. The results of the study show that the ownership status of the contributions purchased for the waqf of cemetery land based on Islamic law belongs to Allah SWT and cannot be owned by anyone. This is in line with the positive law, namely Article 3 paragraph (2) of Government Regulation Number 42 of 2006 concerning the implementation of the Waqf Law considering that Law Number 41 of 2004 concerning Waqf has not specifically regulated the ownership of waqf land. Article 3 paragraph (2) of Government Regulation Number 42 of 2006 stipulates that the registration of waqf property in the name of nazhir does not prove the ownership of nazhir. And in the context of benefits, the management of waqf has not fully fulfilled the recommendations of the Qur'an. So that the waqf that occurs is not in accordance with the applicable laws and regulations. Abstrak. Persoalan wakaf telah diatur dalam Undang-Undang Wakaf. Akan tetapi dengan telah diaturnya persoalan tersebut tidak secara serta merta menghilangkan segala problematika perwakafan, seperti pada persoalan iuran wakaf tanah kuburan. Penelitian ini bertujuan untuk mengetahui praktik atas iuran wakaf dan mengetahui status kepemilikannya atas iuran yang dibelikan tanah di kawasan RW 001 Kelurahan Cigondewah Kaler dengan berdasarkan tinjauan hukum Islam dan Undang-Undang Nomor 41 Tahun 2004 tentang Wakaf. Jenis penelitian ini adalah penelitian kualitatif dengan menggunakan pendekatan normatif empiris. Sumber data yang digunakan adalah data primer dan data sekunder. Pengumpulan data dalam penelitian menggunakan wawancara, observasi dan studi kepustakaan. Hasil penelitian menunjukkan bahwa status kepemilikan atas iuran yang dibelikan untuk wakaf tanah kuburan berdasarkan hukum Islam menjadi milik Allah SWT dan tidak bisa dimiliki oleh siapapun. Hal ini senada dengan hukum positif yakni Pasal 3 ayat (2) Peraturan Pemerintah Nomor 42 Tahun 2006 tentang pelasanaan Undang-Undang Wakaf mengingat Undang-Undang Nomor 41 Tahun 2004 tentang Wakaf belum mengatur secara spesifik mengenai kepemilikan tanah wakaf. Adapun Pasal 3 ayat (2) Peraturan Pemerintah Nomor 42 Tahun 2006 mengatur bahwa terdaftarnya harta benda wakaf atas nama nazhir tidak membuktikan kepemilikan nazhir. Dan dalam konteks kemaslahatan, pengelolaan wakaf belum memenuhi sepenuhnya anjuran Al-Qur’an. Sehingga perwakafan yang terjadi belum sesuai dengan peraturan perundang-undangan yang berlaku.